Enhancing Students’ Learning Motivation Through Social Constructivist Strategies in Al-Qur’an Hadith Instruction - Abdussattar, Muhammad Asyraf; Meti Fatimah; Shahbaz Alam (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study is to describe the application of a social constructivist approach in increasing students' learning motivation in the subject of Al-Qur'an Hadith grade IX at IT Ar-Risalah Sukoharjo Junior High School for the 2024/2025 Academic Year. Theoretical framework: this research is based on social constructivist theory that emphasizes the importance of collaborative and interactive learning, where knowledge is built through social interaction between students with the support of scaffolding and tutoring techniques. Literature review: This study includes a study of the effectiveness of social constructivist approaches in improving motivation and learning outcomes, the importance of collaboration in the learning process, and the role of teachers as facilitators who encourage active student engagement. Methods: This study uses qualitative descriptive methods with data collection techniques in the form of interviews, observations, and documentation to get an in-depth picture of the application of these methods. Results: research shows that the application of a social constructivist approach can significantly increase students' learning motivation through the application of scaffolding, tutoring, and heterogeneous group discussions, which creates an active and enjoyable learning atmosphere. The success of the implementation of this approach is supported by the competence of the principal, the professionalism of teachers, and the availability of adequate infrastructure, although there are obstacles in the form of differences in student abilities and limited learning time. Implications: This study shows that a social constructivist approach can be an effective learning strategy to increase students' motivation and learning achievement, as well as provide an alternative to a more interactive teaching method in learning the Qur'an Hadith. Novelty:  this research lies in the concrete application of a social constructivist approach in the context of learning the Qur'an Hadith, which is still rarely studied, as well as in the identification of supporting factors and obstacles faced in its implementation in the Islamic school environment at the secondary level.